Analisis Yuridis Perlindungan Konsumen terhadap Kerusakan dan Kehilangan dalam Kawasan Parkir: (Studi Putusan Nomor 458 K/Pdt.Sus-Bpsk/2017) - Rudy Hartono; Timoty Nababan; Anggi Pradana Silalahi; Yohannes Paskah Pandowo Siagian (CV Rewang Rencang, 2025)
The purpose of this research by raising a normative legal approach is to reveal the form of legal responsibility of the parking management based on the provisions of laws and regulations. The Supreme Court rejected the cassation filed by PT Nusapala Parkir, reaffirming the responsibility of the parking management to compensate consumers for losses. The analysis shows that parking management must comply with applicable regulations and not use standard clauses that shift responsibility. This research provides insight into the importance of consumer protection and legal responsibility in the parking industry, as well as the pressure on the need for effective law enforcement efforts in protecting consumer rights.